Analisis Pemasaran Produk Murabahah Terhadap Minat Nasabah BMT NU Kasiman Bojonegoro - Sa'adah, Ulfa Ni'matus; Wahyudin, Muhamad; Husaini, Muhammad (Al Iqtishadiyah: Journal of Islamic Economics and Finance, 2024)
Murabahah is a term in Islamic Jurisprudence which means a particular form of buyingand selling when the seller states the cost of purchasing goods, including the price of the goods and other costs incurred to obtain the goods, and the desired level of profit (margin).This research aims to determine the marketing analysis of murabahah products on theinterest of BMT NU Kasiman Bojonegoro customers.This research variable consists of independent variables (independent variables), namelymurabahah products (X1) and promotions (X2) while the dependent dependent variable iscustomer interest (Y). This research method is descriptive quantitative.The results of this research are the marketing of murabahah products and promotion ofmurabahah financing customer interest at BMT NU Kasiman Bojonegoro.